Chemically Reactive Polyurethane–Carbon Nanotube Fiber with Aerogel‐Microsphere‐Thin‐Film Selective Filter. Issue 20 (26th August 2018) - Jeong, Sang‐Mi; Kang, Youngsoo; Lim, Taekyung; Ju, Sanghyun
Abstract: Recently, as the frequency of use of volatile organic compounds (VOCs) in everyday life has increased, there is an increasing interest in chemical sensors that can easily confirm the degree of exposure to VOCs in the surrounding environment in real time. Among the various chemical sensors, the fiber‐type chemical sensor is flexible and lightweight and can be applied to various wearable electronics, such as clothing and ornaments. In this study, a chemically reactive polyurethane–carbon nanotube (PU–CNT) composite fiber coated with an aerogel‐microsphere‐thin‐film (AMTF) is fabricated by using the PU as an insulating body material and CNTs as a 1D conductive material, which provide excellent elasticity and flexibility. The AMTF, which can block liquid‐phase VOCs/water and allow only vapor‐state VOCs to permeate, is introduced to the surface of the sensing channel of the fiber‐type chemical sensor. The PU–CNT composite fiber with the AFMT is able to measure the concentration of various VOCs in water. Thus, it solves the problem that water in contrast to the VOCs to be sensed – cannot be reliably changed by absorption and expansion into the polymer chain when the fiber‐type chemical sensor based on polymer conductive composite materials comes into contact with liquid. Abstract : A chemically reactive polyurethane–carbon nanotube (PU–CNT) composite fiber coated with an aerogel‐microsphere‐thin‐film (AMTF) can measure the concentration of various VOCs in water. The AMTF, which can block liquid VOCs/water and allow only VOC vapor to permeate, is introduced to the surface of the sensing channel of the PU–CNT composite fiber‐type chemical sensor.